Exploring Biological Networks in 3D, Stereoscopic 3D, and Immersive 3D with iCAVE. Issue 1 (9th April 2018) - Kalayci, Selim; Gümüş, Zeynep H.
Abstract: Biological networks are becoming increasingly large and complex, pushing the limits of existing 2D tools. iCAVE is an open‐source software tool for interactive visual explorations of large and complex networks in 3D, stereoscopic 3D, or immersive 3D. It introduces new 3D network layout algorithms and 3D extensions of popular 2D network layout, clustering, and edge bundling algorithms to assist researchers in understanding the underlying patterns in large, multi‐layered, clustered, or complex networks. This protocol aims to guide new users on the basic functions of iCAVE for loading data, laying out networks (single or multi‐layered), bundling edges, clustering networks, visualizing clusters, visualizing data attributes, and saving output images or videos. It also provides examples on visualizing networks constrained in physical 3D space (e.g., proteins; neurons; brain). It is accompanied by a new version of iCAVE with an enhanced user interface and highlights new features useful for existing users. © 2018 by John Wiley & Sons, Inc.